Exemplars of Managing Foreign-Funded Projects: A Case of Government-Owned and Controlled Corporation in Davao del Sur - Lirasan, Ella B.; Lagura, Glenne B. (International Journal of Scientific Research and Management (IJSRM), 2024)
This study examines the exemplary practices of Government-Owned and Controlled Corporation (GOCC) in effectively implementing foreign-funded projects in Davao del Sur. This study employs a qualitative methodology to examine the informant’s experiences, perspectives, and behaviors. The proponent utilized face-to-face, in-depth interviews with eight (8) key informants from the project beneficiaries. They are cooperative officers from project recipients with at least one (1) full term of experience and knowledge in overseeing project implementation. Thematic analysis was used in analyzing the data. The study results highlighted the challenges encountered during project implementation which underlined the importance to develop overcoming mechanisms such as hiring adequate staff for the project, proper training, and provision of adequate budget. This study also highlighted the significance of promoting positive engagement and communication with local communities, government agencies, and project stakeholders to foster trust, acquire feedback, and promptly address concerns. These accentuated that successful implementation of government projects and programs requires thorough planning and collaboration through a well-documented procedure and guidelines, involvement of various stakeholders and a strong sense of teamwork.